Africa : altered states, ordinary miracles - Dowden, Richard, author (New York : PublicAffairs, a Member of the Perseus Books Group, 2009)
Dowden spins tales of cults and commerce in Senegal and traditional spirituality in Sierra Leone; analyzes the impact of oil and the Internet on Nigeria and aid on Sudan; and examines what has gone so badly wrong in Rwanda and the Congo. Contents Africa is a night flight away: images and realities -- Africa is different: Uganda I -- How it all went wrong: Uganda II -- The end of colonialism: new states, old societies -- Amazing, but is it Africa? Somalia -- Forward to the past: Zimbabwe -- Breaking apart: Sudan -- A tick bigger than the dog: Angola -- Missing the story and the sequel: Burundi and Rwanda -- God, trust and trade: Senegal -- Dancers and the leopard men: Sierra Leone -- The positive positive women: AIDS in Africa -- Copying King Leopold: Congo -- Not just another country: South Africa -- Meat and money: eating in Kenya -- Look out world: Nigeria -- New colonists or old friends? Asia in Africa -- Phones, Asians and the professionals: the new Africa.
Keywords: Civilization; Manners and customs; Africa -- Social life and customs -- 20th century